Trends in Gender and Racial/Ethnic Disparities in Physical Disability and Social Support among U.S. Older Adults with Cognitive Impairment Living Alone, 2000–2018 - Shanquan Chen; Huanyu Zhang; Benjamin R. Underwood; Dan Wang; Xi Chen; Rudolf N. Cardinal (Institute of Labor Economics (IZA), 2023)
Informal care is a primary source of support for older adults with cognitive impairment but is less available to those who live alone. We leverage the U.S. Health and Retirement Survey 2000-2018 to examine trends in the prevalence of physical disability and social support among older adults with cognitive impairment living alone, and their gender and racial/ethnic disparities. Information on physical disability and social support was collected through measures of basic and instrumental activities of daily living (BADLs, IADLs). Logistic and Poisson regression were adopted to estimate linear trends over time for binary and integer outcomes, respectively. Among those who reported BADL/IADL disability, the proportion unsupported for BADLs decreased significantly over time, while the proportion unsupported for IADLs increased significantly over time. Among those who received IADL support, the number of unmet IADL support needs increased significantly over time. Over time, Black respondents had a relatively increasing trend of being BADL-unsupported, and Hispanic and Black respondents had a relatively increasing trend in the number of unmet BADL needs, compared to the corresponding trends in White respondents. Our findings may prompt customized interventions to reduce disparities and unmet support needs.
Keywords: I10; J11; J14; J15; J16; 330; social support; physical disability; racial/ethnic disparity; gender disparity; cognitive impairment